Comparative Experimental Study Between Conventional Stepped Solar Still and an Active Stepped Solar Still Incorporated with a Water Circulation System - Abd-Elnaby Kabeel; Hagar Mohamad; Sarah Majeed (Journal of Engineering Research - Egypt, 2019)
In the following experimental study modifications were carried out into a stepped solar still, considerably increasing the distilled water productivity. Objective function in present study is the comparison between of an active stepped solar still provided with modifications in a new water cooling circulation depending upon an active mode by means of a PV cell incorporated for a stepped solar still, with a conventional solar still without water circulation. In the study the results of glass cover temperature, basin temperature, and fresh water productivity are collected for both stepped solar stills. Also, the solar radiation rate for a period of June 2018 to November 2018 have been carried out in order to optimize the stepped still performance and its yield as well. It was found that, these additions and modifications highly enhance the evaporation and condensation, so distillate yield was augmented. It was found that, daily distilled water productivity reached about 7.21 l/m2 day for the stepped solar still with water circulation. While corresponding value was 4.45 l/m2 day for the conventional stepped solar still at the same water depth (2) cm at summer times and 6.41 l/m2 day for the stepped solar still with water circulation and 3.5 l/m2 day for the conventional stepped solar still at winter times also at the same water depth. The increase in daily distillate water productivity for a stepped solar still with a PV and water circulation is about 78.24 % higher than that of a conventional stepped solar still. Moreover, the average efficiency of daily freshwater productivity is 42.84 % for a stepped solar still with water circulation, while it was 37 % for a conventional stepped solar still, at the same water depth 2 cm at summer and 40.5 % for a stepped solar still with water circulation and 34 % for a conventional stepped solar still at winter times. The present study held under the climate conditions of Egypt at Faculty of Engineering-Tanta University, Egypt.